Production of aragonite whiskers by carbonation of fine recycled concrete wastes: An alternative pathway for efficient CO2 sequestration - Shen, Peiliang; Jiang, Yi; Zhang, Yangyang; Liu, Songhui; Xuan, Dongxing; Lu, Jianxin; Zhang, Shipeng; Poon, Chi Sun (Renewable & sustainable energy reviews, 2023)
In this study, a wet carbonation method targeting high carbonation rate was developed to prepare aragonite whisker using fine recycled concrete waste (FRCW), aiming to effectively capture CO2 and convert FRCW into high-value products. The effect of operational factors, including MgCl2 concentration, temperature, CO2 concentration and duration on the formation of aragonite was systemically investigated. The results indicated this carbonation process can not only produce needle-like aragonite whisker-rich materials but also capture a large amount of CO2 (0.19 g CO2 per g FRCW) within an hour. The MgCl2 concentration and temperature were key parameters governing the nucleation of aragonite, while the formation of needle-like aragonite was favored in a MgCl2-FRCW suspension with a minimum Mg2+/Ca2+ molar ratio >0.16 at a temperature >60 °C. A lower CO2 concentration of <50% only slightly decreased the carbonation rate without affecting the types of carbonation products formed, indicating the potential to sequestrate CO2 from industrial flue gas directly. In addition, amorphous carbonation phases including silica gel, decalcified C–S–H and amorphous calcium carbonate were produced apart from the dominant reaction product-aragonite. Based on the results, the formation of aragonite could be divided into two steps: 1. The FRCW reacted with MgCl2 to form a new FRCW-MgCl2-Mg(OH)2–CaCl2 system. 2. The Ca2+ reacted with CO32− to form aragonite and brucite was solubilized back to MgCl2, resulting in possible recycling and reusing MgCl2 for another carbonation cycle. The proposed approach exhibits a novel direction of sequestering CO2. •An alternative pathway for efficient CO2 sequestration was provided.•Needle-like aragonite with a length of 10–30 μm and diameter of 1–3 μm was prepared.•The approach promotes the reuse of fine recycled concrete waste (FRCW) and sequesters CO2.•Carbonation kinetics and nucleation of aragonite was evaluated.